Angiogenesis in Adipose Tissue - Cao, Yihai.; Cao, Yihai. (Springer New York : Imprint: Springer, 2013)
Angiogenesis has recently played a critical role in regulation of adipose tissue expansion and regression.  Like most other tissues in the body, adipose expansion and regression is accompanied by alteration of blood vessel density and structures. The vascular alteration plays an active role in regulation of adipose tissue size and functions.   Targeting blood vessels in the adipose tissue have demonstrated to be a novel approach for possibly treatment of cancer, obesity and other metabolic diseases. This book provides the most updated information on this type research and discusses future opportunities for therapy.